ANALISIS PENDAPATAN PEDAGANG KAKI LIMA (PKL) DI KOTA GORONTALO - Ramlah Alkatiri; Agus Salim Lamusu (JPPE : Jurnal Perencanaan & Pengembangan Ekonomi, 2022)
This study aims to determine 1) the effect of trading time on the income of street vendors in Gorontalo City, 2) the effect of business time on the income of street vendors in Gorontalo City and 3) the effect of business capital on the income of street vendors in Gorontalo City. This research uses a descriptive quantitative approach involving 31 street vendors in Gorontalo City as respondents. The data used are primary data obtained from a questionnaire with Likert scale criteria. The analysis technique uses multiple regression followed by partial hypothesis testing (t test) and simultaneous hypothesis testing (F test), while the data processing used is SPSS version 16. The results of this study indicate that there is a significant effect of trading time, business time and business return as independent variables simultaneously (together) on the income of street vendors as the dependent variable. Meanwhile, the results of the partial test of the hypothesis (T test) indicate that trading time has a positive and significant effect on the income of street vendors, the length of business does not affect the income of street vendors, while working capital has a negative and insignificant effect on the income of street vendors.This study aims to determine 1) the effect of trading time on the income of street vendors in Gorontalo City, 2) the effect of business time on the income of street vendors in Gorontalo City and 3) the effect of business capital on the income of street vendors in Gorontalo City. This research uses a descriptive quantitative approach involving 31 street vendors in Gorontalo City as respondents. The data used are primary data obtained from a questionnaire with Likert scale criteria. The analysis technique uses multiple regression followed by partial hypothesis testing (t test) and simultaneous hypothesis testing (F test), while the data processing used is SPSS version 16. The results of this study indicate that there is a significant effect of trading time, business time and business return as independent variables simultaneously (together) on the income of street vendors as the dependent variable. Meanwhile, the results of the partial test of the hypothesis (T test) indicate that trading time has a positive and significant effect on the income of street vendors, the length of business does not affect the income of street vendors, while working capital has a negative and insignificant effect on the income of street vendors.